Inspiring Students' Moral Imagination: Mission and Process (Global Journal of Human-Social Science, 2024)
In diverse academic environments, there is an evocative moral question that is tacitly held but rarely voiced: "Who matters?" The answer reflects the circle of moral concern that educators and students hold for themselves, their school, and their community. The enduring challenge confronting educators is how to inspire students to enlarge their circles of moral concern through instructional practices, including: Teacher as Moral Leader, Self-Governing Professionalism, Values-Based Student Conduct, and Teaching and Learning through Visual Imagery.